Impact of elicitors (alginate, Bacillus cereus, and cholesterol) on the production of secondary metabolite (lovastatin, (+)-geodin, and sulochrin) by Aspergillus terreus ATCC 20542 during submerged fermentation - Mohd Zaini, Nurul Solehah; Hasan, Hanan; Abbas, Ali; Montoya, Alejandro; Abd Rahim, Muhamad Hafiz (Elsevier Ltd, 2024)
This study explored the impact of elicitors (sodium alginate (SA), microbial contamination in the form of Bacillus cereus (MC), and cholesterol) on the synthesis of lovastatin, (+)-geodin, and sulochrin by A. terreus during a 9-day period. Lovastatin production significantly increased with SA (200 mg/50 mL) and MC by approximately 5-fold at the end of fermentation, with significant increments observed as soon as day 3. In contrast, (+)-geodin production decreased (SA by 454 and MC by 138), and sulochrin's pattern showed no clear concentration dependence. Gelatine, used as a viscosity control for SA, reduced all metabolites but improved biomass, indicating viscosity's negative impact on production. Cholesterol significantly increased lovastatin (18.68 mg/L, a 77.31 increase), though lower than SA and MC, and induced ∼2.6-fold higher (+)-geodin and sulochrin on day 9 at 200 mg/50 mL. In general, sulochrin levels were significantly higher with all elicitors, except for gelatine, on day 9. All elicitors induced changes in metabolite production compared to negative control, but their mechanisms differed. SA and MC primarily influenced lovastatin, showing rapid production as early as day 3. In contrast, cholesterol enhanced A. terreus morphology (small, compact and hairy), leading to an increase in metabolite production, although to a lesser extent than SA and MC.